2020
DOI: 10.3390/toxins12100644
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Probabilistic Risk Assessment of Fumonisin B1, Fumonisin B2 and Deoxynivalenol in Nixtamalized Maize in Mexico City

Abstract: Fumonisins (FB1+FB2) and deoxynivalenol (DON) are mycotoxins produced by Fusarium species that might be present in maize and maize products. Knowledge on their occurrence in nixtamalized maize from Mexico together with an accompanying risk assessment are scarce, while nixtamalized maize is an important food in Mexico. This study presents the occurrence of FB1 + FB2 and DON in nixtamalized maize samples collected in Mexico City and analyses their distribution and resulting estimated daily intake for Mexican con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Alternatively, the QuEChERS method, initially developed for pesticides, was subsequently introduced for the dispersive solid-phase extraction (SPE) of FB1 [46], and further validated for its application in the multi-target analysis due to its lower cost, less time consumption, easy procedure [50,52,63,185,186], as well as its availability in extraction kits [54] with satisfactory recoveries [60]. Likewise, sample preparation with a QuEChERS dispersive SPE was useful for minimization of matrix effects from beer, with a preconcentration step producing enhanced LODs [74].…”
Section: Chromatographic Detection Of Fumonisin B1mentioning
confidence: 99%
“…Alternatively, the QuEChERS method, initially developed for pesticides, was subsequently introduced for the dispersive solid-phase extraction (SPE) of FB1 [46], and further validated for its application in the multi-target analysis due to its lower cost, less time consumption, easy procedure [50,52,63,185,186], as well as its availability in extraction kits [54] with satisfactory recoveries [60]. Likewise, sample preparation with a QuEChERS dispersive SPE was useful for minimization of matrix effects from beer, with a preconcentration step producing enhanced LODs [74].…”
Section: Chromatographic Detection Of Fumonisin B1mentioning
confidence: 99%
“…Furthermore, total fumonisin levels ranged from 0.28 to 15 mg/kg with a mean of 1.54 ± 0.12 mg/kg, and 20% of the prepared feed samples randomly collected from 133 commercial poultry farms, 76 feed processors and 8 feed vendors of Ghana were higher than the FAO/WHO maximum tolerable daily intake limit of 2 mg/kg [11]. Studies also revealed that 47% of Mexican men and 30% of Mexican women might exceed the provisional tolerable daily intake (PMTDI) of 2 µg/kg bw/day Toxins 2022, 14, 0 2 of 12 for FBs [12]. Aspergillus niger, intended for use in the food industry in China, can cause dynamic FB2 production to reduce human exposure to FBs [13].…”
Section: Introductionmentioning
confidence: 98%
“…Toxins 2022, 14, x FOR PEER REVIEW 2 of 12 women might exceed the provisional tolerable daily intake (PMTDI) of 2 μg/kg bw/day for FBs [12]. Aspergillus niger, intended for use in the food industry in China, can cause dynamic FB2 production to reduce human exposure to FBs [13].…”
Section: Introductionmentioning
confidence: 99%
“…The EDI comprises a combination of food consumption data, typical contamination levels, and consumer body weight. Although previous surveys have shown that FB exposure levels in many countries, including Tanzania, Somalia, Mexico, and Brazil, exceeded the PMTDI [ 24 , 25 , 26 , 27 ], indicating potential health risks from dietary exposure to different food products, few studies have assessed the potential human health risks of consuming PFT contaminated with FBs. To the best of our knowledge, the risk assessment of FBs in PFT in Guangxi has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%